Evaluation of Development and Implementation of Hospital Formulary for Paediatric Department in a Rural Tertiary Care Teaching Hospital of South India - BJ, Mahendra Kumar; M, Sowmya; D, UmaMaheswari; R, Hymavathi; S, Ramesh (Indian Journal of Pharmacy Practice)
Formulary is a continually revised compilation of pharmaceuticals and some important ancillary information that reflects the current clinical judgement of medical staff. This prospective survey study was carried out to develop a Hospital Formulary for the rural tertiary care teaching hospital. Well designed suitable questionnaires were piloted and given to the staff of Paediatric Department. Drug list was prepared and monographs were developed accordingly. The developed Paediatric Formulary was implemented in the Department of Paediatrics and later evaluated by using suitably designed feedback questionnaire. Prepared paediatric hospital formulary consisted of 102 drugs of various categories. Availability of brands was from single to many and 49 brands of drug combinations were present. The prepared paediatric hospital formulary was implemented in the hospital. The staff and postgraduate students of Department of Paediatrics were very satisfied with the implemented formulary and appreciated that the work was carried out to a great level. This provides them updated unbiased information about the drugs and available brands with cost in the hospital pharmacy. This formulary promotes the safe and effective use of medicines thereby reducing the total cost of treatment of the patient.
Keywords: Best practice; Drug list; Formulary; Questionnaires